Los empresarios argentinos frente a las relaciones comerciales y diplomáticas con China: un acercamiento a las bases económico-sociales de la política exterior del gobierno de Cambiemos, 2016- 2019 - Sanz Cerbino, Gonzalo; Rodríguez Nievas, Victoria; Grimaldi, Nicolás; Toro Tesini, María del Rosario (El Colegio de México A.C., 2022)
In recent decades, Argentina intensified trade and diplomatic relations with China. Despite the switch in foreign policy resulting from the change in president of 2015, China kept its place in our system of international alliances. These continuities reveal the existence of socio-economic interests that transcend the political or ideological stances of each administration. With the aim of revealing these interests, this article seeks to reconstruct the positions taken by the Argentine business community with respect to the Sino-Argentine bilateral relationship between 2016 and 2019, and their influence on foreign policy. Drawing on the theoretical-methodological contributions of the school of international political economy (IPE), we will analyze the statements and actions of Argentina's main business organizations and their impact on foreign relations, contrasting the information obtained with statistical data regarding bilateral trade between the two countries.